Tracking of cardiorespiratory fitness in Japanese men - Naofumi Yamamoto; Susumu S. Sawada; I-Min Lee; Yuko Gando; Ryoko Kawakami; Haruka Murakami; Motohiko Miyachi; Yutaka Yoshitake; Hidenori Asai; Takashi Okamoto; Koji Tsukamoto; Hiroaki Tanaka; et al. (The journal of physical fitness and sports medicine, 2018)
The stability of the relative order of cardiorespiratory fitness (CRF) during adulthood has not been sufficiently investigated. This study investigated the tracking of CRF over a 7-year follow-up period in Japanese male adults aged 18-53 years. A total of 3,718 male workers who underwent three submaximal exercise tests (a first test and again 3 and 7 years later for a second and third test) were included. CRF was defined as the maximal oxygen uptake estimated from a submaximal exercise test using a cycle ergometer. Spearman correlation coefficients for CRF in the first and second tests, the second and third tests and the first and third tests were 0.61, 0.62 and 0.54, respectively. A moderate kappa coefficient, indicating the degree of agreement for quartiles, was obtained for all follow-up periods (kappa coefficient = 0.43-0.53). The changes in quartiles for all three time measurements indicated that approximately 70% of participants had stable (participants in the same quartile for all three measurements) or moderately stable (participants who exhibited changes varying by one quartile from the initial quartile) CRF levels. These findings showed moderate CRF tracking during adulthood over a period of up to 7 years.